2009
DOI: 10.1073/pnas.0812297106
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association analysis reveals a SOD1 mutation in canine degenerative myelopathy that resembles amyotrophic lateral sclerosis

Abstract: Canine degenerative myelopathy (DM) is a fatal neurodegenerative disease prevalent in several dog breeds. Typically, the initial progressive upper motor neuron spastic and general proprioceptive ataxia in the pelvic limbs occurs at 8 years of age or older. If euthanasia is delayed, the clinical signs will ascend, causing flaccid tetraparesis and other lower motor neuron signs. DNA samples from 38 DM-affected Pembroke Welsh corgi cases and 17 related clinically normal controls were used for genome-wide associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
344
1
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(363 citation statements)
references
References 37 publications
(56 reference statements)
10
344
1
8
Order By: Relevance
“…Several causes of DM have been proposed, including immunologic [5,19], metabolic [9], and genetic mechanisms [4]. Recently, Awano et al indicated that a superoxide dismutase 1 (SOD1) mutation (c.118G>A) is associated with canine DM in several breeds including PWC [4,17].…”
mentioning
confidence: 99%
“…Several causes of DM have been proposed, including immunologic [5,19], metabolic [9], and genetic mechanisms [4]. Recently, Awano et al indicated that a superoxide dismutase 1 (SOD1) mutation (c.118G>A) is associated with canine DM in several breeds including PWC [4,17].…”
mentioning
confidence: 99%
“…Concernant les maladies à composantes génétiques « simples » ou supposées simples, de nombreux travaux font actuellement état de l'identification de gènes responsables d'affections partagées entre l'homme et le chien, comme, par exemple, des rétinopa-thies (Wilk et al 2008), la sclérose amyothrophique latérale (Awano et al 2009), des maladies cardiaques (Meurs et al 2010), les lipofuscinoses neuronales canines (Abitbol et al 2010 ;Katz et al 2011), les épilepsies (Lohi et al 2005 ;Sepalla et al 2011), des maladies dermatologiques telle que l'ichtyose (Grall et al 2012), ou encore des anomalies comme le phénotype sans poil des chiens nus (Drogemuller et al, 2008).…”
Section: Identification Des Bases Génétiques De Maladies D'intérêt Chunclassified
“…A relevant animal model should show behavioral deficits that resemble symptoms in patients. Some animal models reproduce the human condition quite faithfully, as in the case of familial ALS in which the same mutations that are found in human disease produces a similar progressive loss of neurons and motor function in dogs [22], rats [23], and mice [24]. Models of injury, such as spinal cord injury and stroke, can be induced in animals and are used extensively to evaluate treatments for both acute and chronic dysfunction in patients.…”
Section: Preclinical Animal Modelsmentioning
confidence: 99%